A New Era of Epidemiology: Digital Epidemiology for Investigating the COVID-19 Outbreak in China - He, Zonglin; Zhang, Casper J P; Huang, Jian; Zhai, Jingyan; Zhou, Shuang; Chiu, Joyce Wai-Ting; Sheng, Jie; Tsang, Winghei; Akinwunmi, Babatunde O; Ming, Wai-Kit (Journal of medical Internet research, 2020)
A novel pneumonia-like coronavirus disease (COVID-19) caused by a novel coronavirus named SARS-CoV-2 has swept across China and the world. Public health measures that were effective in previous infection outbreaks (eg, wearing a face mask, quarantining) were implemented in this outbreak. Available multidimensional social network data that take advantage of the recent rapid development of information and communication technologies allow for an exploration of disease spread and control via a modernized epidemiological approach. By using spatiotemporal data and real-time information, we can provide more accurate estimates of disease spread patterns related to human activities and enable more efficient responses to the outbreak. Two real cases during the COVID-19 outbreak demonstrated the application of emerging technologies and digital data in monitoring human movements related to disease spread. Although the ethical issues related to using digital epidemiology are still under debate, the cases reported in this article may enable the identification of more effective public health measures, as well as future applications of such digitally directed epidemiological approaches in controlling infectious disease outbreaks, which offer an alternative and modern outlook on addressing the long-standing challenges in population health.